2022
DOI: 10.1017/s0007114522000691
|View full text |Cite
|
Sign up to set email alerts
|

The associations of soya intakes with non-communicable diseases: a scoping review of meta-analyses

Abstract: This scoping review aimed to identify published meta-analyses of the associations of dietary soy intakes with cardiovascular, cancer, and diabetes II diseases and the best relative risk estimates. A published novel assessment process combining the well-validated Cochrane Review measures, the AMSTAR 2 checklist, and a published algorithm specifically designed for conducting a scoping review of similar meta-analyses was employed. This scoping review identified and evaluated 28 meta-analysis reports, published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The actual intake amount of soy products was higher than that of pickled food and processed meat products. Many studies found that a higher intake of soy products could decrease the risk of gastric cancer ( 25 , 26 ). Therefore, the promoting effect of pickled food and processed meat products on the risk of gastric cancer may be covered by the protective effect of soy products on the risk of gastric cancer in this dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The actual intake amount of soy products was higher than that of pickled food and processed meat products. Many studies found that a higher intake of soy products could decrease the risk of gastric cancer ( 25 , 26 ). Therefore, the promoting effect of pickled food and processed meat products on the risk of gastric cancer may be covered by the protective effect of soy products on the risk of gastric cancer in this dietary pattern.…”
Section: Discussionmentioning
confidence: 99%